O papel das entidades contábeis e a educação continuada no processo de atualização do contabilista: um estudo exploratório - Gilioli, Adriano (2011)
The current operational environment of companies, characterized by fierce competition, has required all its actors to rethink the validity of the strategies, postures and rocedures so far adopted by management. Accountants have also had to extend their skills to efficiently meet the demands of this new environment. Personal skills, knowledge of the business and a more active participation in the management process began to be a part of the accountant s new profile. Taking this reality into account, this moment makes a diagnosis of the accountant s profile in the present and identifies to what extent it is consistent with these new requirements. Using an exploratory and descriptive research methodology, an empirical inquiry was conducted with 83 accountants. For the data collection a questionnaire with closed questions was used. In the data classification the article applies descriptive statistics, which is the basis for the qualitative analysis. Its results show that the accountants training is still focused on the technical aspects, with little priority given to the improvement of other skills. They also show that the accountant s participation in the decision making process of the organizations is still below of what is recommended by the literature and continued education whereby fountain of knowledge